Multisectoral approach for promoting public health - Subhash Salunke; Dharmesh Kumar Lal (Wolters Kluwer Medknow Publications, 2017)
Multisectoral approach (MSA) refers to deliberate collaboration among various stakeholder groups (e.g., government, civil society, and private sector) and sectors (e.g., health, environment, and economy) to jointly achieve a policy outcome. By engaging multiple sectors, partners can leverage knowledge, expertise, reach, and resources, benefiting from their combined and varied strengths as they work toward the shared goal of producing better health outcomes. Improving public health (PH) is challenging because of the size of its population and wide variation in geography. MSA help in addressing identified health issues in focused way as it helps in pooling the resources and formulating the common objectives. One of the major advantages is optimization of usage of resources by avoiding duplication of inputs and activities which tremendously improve program effectiveness and efficiency. Willingness at the leadership and mandate at the policy level are necessary to plan and execute the successful multisectoral coordination. All the major stakeholders require to share the common vision and perspective. Developing institutional mechanism is utmost requirement as it will standardize the processes of intersectoral coordination (ISC). Creation of PH cadre is strategic move to meet the major health challenges being faced by the health system, and it would be anchor of establishing systematic ISC. There are many national and international examples of MSA applications such as for malaria elimination, tobacco control, HIV/AIDS prevention, Finland's community-based cardiovascular disease prevention project (North Karelia Project), and Singapore's Health Promotion Board. Promotion of MSA within the health system and with other ministries is seen as an important measure for effective implementation and improving efficiency.